Biosorption of chromium (VI) ions using sustainable eggshell impregnated pandanus amaryllifolius roxb. biosorbent - Noor Yahida, Yahya; Chan, J. X.; N., Ngadi (Novel Carbon Resource Sciences, 2021)
Currently, wastewater containing heavy metals treatment has been included as a significant topic for research. This is due to the effluent that is concentrated with a toxic and hazardous content which needs for a proper treatment as to reduce the environmental impacts before it can be released as an effluent. Therefore, biosorption by waste material was proposed in this study as a treatment method for this type of wastewater. The objective is focus on the comparison of the characteristics and performance of raw eggshell waste biosorbent with prepared hybrid eggshell pandan biosorbent on the removal of Cr (VI) ions in aqueous solution. From the study, it showed that the prepared hybrid biosorbent perform higher percentage in the removal of Cr (VI) ions in aqueous solution compare to the raw eggshell waste with its optimum condition at 140 min of contact time, 0.5 g of biosorbent dosage at 50 °C and pH 4 in 0.8 mg/L of solution concentration. On the other hands, the optimum conditions for the raw eggshell waste biosorbent to achieve its highest percentage removal of Cr (VI) ions in aqueous solution is 140 mins of contact time, 0.5 g of biosorbent dosage in room temperature at pH 5 in 0.8 mg/L of solution concentration. The kinetic study revealed that the adsorption model of this study follows the pseudo-second-order kinetic model of Legergren with positive value of enthalpy (16.68 kJ/mol) and entropy change (0.0473 kJ/mol). In addition, hybrid eggshell-pandan biosorbent has a potential to become a candidate of biosorbent to the removal of Cr (VI) ions in wastewater.